THE ROLE OF PANCASILA LEARNING IN DEVELOPING SOCIO POLITICAL AWARENESS AMONG P.IPS UIN MALANG STUDENTS - Risky Alamsyah; Muhammad Rizal Firdaus; Rifa Arum Tazkya Maharani; Deliana Putri; Ahmad Farhan Abdilla (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This research highlights the strategic role of Pancasila learning in developing social and political awareness among students of Social Science Education Study Program (P.IPS) at Maulana Malik Ibrahim State Islamic University Malang. The background of this research is rooted in the low level of participation and awareness of social and political issues among the younger generation in the midst of globalization. To understand this phenomenon, the research used a descriptive qualitative approach with field research methods through structured interviews and direct observation. Social awareness indicators were measured based on the theory of Yoyo Sudaryo and Agus Ribowo, while political awareness refers to the theory of Almond and Verba. The data were then analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and inference. The results showed that Pancasila learning is able to increase students' social and political awareness through the internalization of values such as empathy, honesty, tolerance, and active participation in community life. In addition, this learning also encourages students' participation in political activities, strengthens their awareness of their rights and responsibilities as citizens, and forms a critical attitude toward various social issues. The implications of the results of this study indicate the importance of strengthening Pancasila learning as a character building tool for students who are active, critical, and empowered to face socio-political challenges in the future.